A novel missense mutation of CMT2P alters transcription machinery. Issue 6 (27th September 2016) - Hu, Bo; Arpag, Sezgi; Zuchner, Stephan; Li, Jun
Abstract : Objective: Charcot–Marie–Tooth type 2P (CMT2P) has been associated with frameshift mutations in the RING domain of LRSAM1 (an E3 ligase). This study describes families with a novel missense mutation of LRSAM1 gene and explores pathogenic mechanisms of CMT2P. Methods: Patients with CMT2P were characterized clinically, electrophysiologically, and genetically. A neuronal model with the LRSAM1 mutation was created using CRISPR/Cas9 technology. The neuronal cell line along with fibroblasts isolated from the patients was used to study RNA‐binding proteins. Results: This American family with dominantly inherited axonal polyneuropathy reveals a phenotype similar to those in previously reported non‐US families. The affected members in our family cosegregated with a novel missense mutation Cys694Arg that alters a highly conserved cysteine in the RING domain. This mutation leads to axonal degeneration in the in vitro neuronal cell line. Moreover, using protein mass spectrometry, we identified a group of RNA‐binding proteins (including FUS, a protein critically involved in motor neuron degeneration) that interacted with LRSAM1. The interactions were disrupted by the Cys694Arg mutation, which resulted in reduction of intranuclear RNA‐binding proteins. Interpretation: Our findings suggest that the mutant LRSAM1 may aberrantly affect the formation of transcription machinery. Given that a similar mechanism has been reported in motor neuron degeneration of amyotrophic lateral sclerosis, abnormalities of RNA/RNA‐binding protein complex may play a role in the neuronal degeneration of CMT2P. Ann Neurol 2016;80:834–845